Absurdity of Society in Edward Albee: Examining the Fragility of Democracy in American Society (Journal of Advances and Scholarly Researches in Allied Education, 2017)
These words were spoken by Edward Albee in 1998, in his “Speech to the American Council for the Arts”. The address makes it clear that Albee is concerned with the “societal and cultural health” (SMM 194) of the American civilization. The lecture focuses on various aspects which are disturbing the placidity of American society. The first idea Albee is concerned with is the passivity of American society. He said that only forty-nine percent of people voted in the last election held in 1994, which means that the civilization is governed by the will of half of the potential electorate. So, he is concerned with the passivity of society and this fragile democracy.